The effects of admonishment on statute of limitations in tax law - Đokić Minja (Anali Pravnog Fakulteta u Beogradu)
The scope of analysis in this article is an issue that has been disputed in practice. We ask ourselves does admonishment for tax debt interrupt the term of statute of limitations in tax law ? Author has analysed the statute of limitations in tax law through legal practice of tax authorities (official oppinions of the Ministry of finance regarding the issue at hand) and judicial practice (Supreme court and the Constitutional court). It has been established that there is a difference in understanding the institute of admonishment and its application. It has also been established that, in spite of the fact that tax authorities do not consider admonishment as a tax administrative act or addressing legal act, it is interpreted as sufficient to break the term of statute of limitations. We shall prove that delivery of admonishment to a tax payer does not interrupt or break the term of statute of limitations because it is not an addressing legal act, which is expressly demadned by the law.